2020
DOI: 10.1177/1535370220962043
|View full text |Cite
|
Sign up to set email alerts
|

Secondary hemophagocytic lymphohistiocytosis versus cytokine release syndrome in severe COVID-19 patients

Abstract: COVID-19 or SARS-CoV-2 infection can lead to severe acute respiratory distress syndrome/pneumonia with features of cytokine storm reminiscent of secondary hemophagocytic lymphohistiocytosis (HLH), which can be diagnosed by the calculated HScore. Recent reports have suggested favorable responses to the interleukin-1 receptor antagonist, anakinra in patients with COVID-19 associated secondary HLH. In our single institution study, we compared 14 COVID-19 cytokine storm patients with 10 secondary HLH patients seen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
30
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(31 citation statements)
references
References 22 publications
0
30
0
Order By: Relevance
“…In children with MIS-C there was a significant reduction of lymphocytes and platelets as compared to the COVID-19 group. Notably lymphopenia and thrombocytopenia are also typical of the hyperinflammatory form of COVID-19 in adults (7,12). The analysis of the plasmatic levels of inflammatory chemokines and cytokines in patients with COVID-19 and MIS-C showed higher levels of IL-6, CXCL8, CCL2/MCP-1, CXCL9/MIG, and CXCL10/IP-10 in MIS-C, whereas CCL5 levels were significantly higher in the COVID-19 group.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…In children with MIS-C there was a significant reduction of lymphocytes and platelets as compared to the COVID-19 group. Notably lymphopenia and thrombocytopenia are also typical of the hyperinflammatory form of COVID-19 in adults (7,12). The analysis of the plasmatic levels of inflammatory chemokines and cytokines in patients with COVID-19 and MIS-C showed higher levels of IL-6, CXCL8, CCL2/MCP-1, CXCL9/MIG, and CXCL10/IP-10 in MIS-C, whereas CCL5 levels were significantly higher in the COVID-19 group.…”
Section: Discussionmentioning
confidence: 93%
“…COVID-19 adult patients, who develop the most severe disease, usually display a hyper-inflammatory state, resembling secondary hemophagocytic lymphohistiocytosis (sHLH) (6,7). There is also evidence that critically ill COVID-19 patients, as measured based on PaO2/FiO2 ratio (<200) (8,9), display higher plasmatic levels of chemokines (CXCL8, CXCL9, CXCL10), cytokines (IL-6, IL-10), and reactive oxygen species (ROS), bringing attention to the role of the host immune system in developing infection-related complications (10,11).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Autopsy studies demonstrated a high percentage of hemophagocytosis in COVID-19 patients' bone marrow, pulmonary lymph nodes, or spleen, ranging from 75 to 94% (87,88). Using a validated hemophagocytic syndrome diagnostic score (HScore) cut-off point of 168 (89), we identified a total of 15 cases of COVID-19-associated HLH ( Table 3) (88,(90)(91)(92)(93)(94). However, the reported prevalence of HLH in severe COVID-19 patients was as low as 7% (93,94).…”
Section: Hemophagocytic Lymphohistiocytosis (Hlh)mentioning
confidence: 99%
“…Using a validated hemophagocytic syndrome diagnostic score (HScore) cut-off point of 168 (89), we identified a total of 15 cases of COVID-19-associated HLH ( Table 3) (88,(90)(91)(92)(93)(94). However, the reported prevalence of HLH in severe COVID-19 patients was as low as 7% (93,94). Notably, routine examinations for serum triglycerides and fibrinogen, hepatosplenomegaly, or tissue hemophagocytosis were not always performed in these studies.…”
Section: Hemophagocytic Lymphohistiocytosis (Hlh)mentioning
confidence: 99%